Identification of Coastal Seawater Intrusion in North Java Using Vertical Electrical Sounding (VES): A Case Study of Suradadi District, Tegal, Central Java - Yustisio Dianwiyono; Azriel Ihza Putra Augustria; Dhiyatamma Purusa Wiradityo; Bayu Majid Destianto; Nur Ahmad Roihan (Journal of Social Research, 2025)
Suradadi District is one of the districts in Tegal Regency, located in the Pantura (North Coast) area of Java. The availability of clean water is a significant issue in coastal regions, as wells that have been dug often yield brackish to saline water. The objective of this study is to identify the distribution of seawater intrusion in the coastal area of Suradadi District, Tegal Regency. The method employed is the Vertical Electrical Sounding (VES) geoelectrical method at five measurement points, each spaced approximately 600 meters apart. Data acquisition was carried out at five parallel lines, with point spacing ranging from 300 to 1000 meters. Seawater intrusion in the study area is widespread, extending up to approximately ±2300 meters inland from the coastline. Intrusion was identified at depth intervals as follows: point 1 at depths of 0.5–27 meters, point 2 at 1–27 meters, point 3 at 3.5–13 meters, point 4 at 10–14 meters, and point 5 at 14–17 meters. The extent of intrusion in this area is primarily attributed to the lithological composition, which is dominated by alluvial deposits consisting of sand, silt, and clay.